Coopetition in for-profit and non-profit organizations - micro level - Moczulska Marta; Seiler Bartosz; Stankiewicz Janina (Management)
A situation in which appears at the same time a competition and cooperation between the subjects is defined as a coopetition. First of all it is considered at the mezo level – between the companies, but it can be analysed at the micro level – inside the organization. In the second case, it concerns shaping the relations among the employers which compete one with another and at the same time they cooperate. Among the organizations where the coopetion can be analysed we distinguish two types - for profit and non profit. A difference of the functioning of the for profit and non profit organizations can be seen among other things in the differences that refer to the shape of the coopetition. In the article the characteristic of a intraorganizational coopetition in the for profit and non profit subjects was presented. The base to formulate the conclusions was formed by the investigations made in which, to collect the data there were used the semistructure interviews with six sample selected organizations – three for profit and three non profit.